“Let Alone at Miss Universe”: Siera Bearchell as Embodiment of Cultural Resistance of Femininity in Miss Universe - Quamilla, Asyifa (Universitas Sebelas Maret, 2022)
The existence of plus size contender in Miss Universe has broken down the normalization of slenderness which has been one of manifestations of femininity in American society and its beauty pageant industries. The plus size lens is brought by Siera Bearchell who has been placed on Top 9 in Miss Universe 2016 edition to resist the cultural normalization of slender body size. By using textual analysis, this research focuses on Siera Bearchell’s YouTube videos and news articles related to the plus size contender to investigate the way she embodies the cultural resistance through her personal practices in the Miss Universe pageant. This research shows that Siera Bearchell has failed at embodying the dominant ideology of feminine slender ideal in Miss Universe. However, this failure cannot put Siera Bearchell to cultural obedience to the bodily ideal. This occurs since Siera Bearchell has resisted the cultural normalization by embodying her plus size body as a state for personal space and freedom. Therefore, the symbol of normalization of feminine slender size contradicts her identity as the plus size contender. Ultimately, this research shows that the existence of plus size contender in Miss Universe has been a symbol of cultural resistance of femininity in the American beauty pageant.